Hubungan Kelahiran Prematur dengan Kejadian Ikterus Neonatorum pada Bayi Baru Lahir di RSUD - Baiq Disnalia Siswari; Eka Mustika Yanti; Baiq Eva Priyatna (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
According to data from the World Health Organization (WHO), the infant mortality rate (IMR) in the world in 2012 was 49 per 1000 live births, high risk infant or infant factors that increase the risk of perinatal or neonatal death is one of them is jaundice neonatorum or jaundice. neonatorum is the cause of neonatal death about 20-40% of all deliveries. Based on the results of a preliminary study conducted at the hospital, from 120 cases of premature birth there were 32 cases of neonatal jaundice. This study was to determine the relationship between premature birth and the incidence of neonatal jaundice in newborns. This type of research is correlational analytic with a case control design. The number of samples used in this study is 55 people in the case group and 55 people in the control group. The analysis used is univariate analysis and bivariate analysis. based on the results of statistical test analysis, it was found that in the case group or mothers who experienced premature birth, there were 32 babies (58.2%) who had neonatal jaundice and in the control group or the group of mothers who did not experience premature birth, they got 14.infants or (25.5%) who had neonatal jaundice. the results of the chi square test obtained a p-value of 0.001, it can be concluded that there is a significant relationship between premature birth and the incidence of neonatal jaundice. it is hoped that pregnant women will continue to routinely carry out antenatal care to prevent premature birth, for further researchers to be able to look for other variables related to the incidence of neonatal jaundice.